Lateral Meander Migration of a Medium-sized Lowland River: Case Study on the Rába River, Hungary - Pusztai-Eredics, Alexandra; Kovács, Gábor; Tóth, Gábor; Lenner, Tibor; Kiss, Tímea (Geographica Pannonica, 2024)
Engineering works greatly influence the lateral channel migration (LCM) of meandering rivers. We aimed to characterise the spatiotemporal characteristics of LCM during the last 174 years of the almost freely meandering Upper Rába (Hungary) and to identify units with distinctive LCM histories. The studied Rába’s reach has been regulated just at some points. Due to the free meandering, its length varied between 119 and 133 km. The most intensive length increase (+291 m/y) took place between 2005 and 2008, and by the end of the process, the sinuosity had reached its historical maximum (SI2018= 1.93). The mean LCM was 3.3 m/y (1844–2018). The periods with intensive channel migration (max: 24–27 m/y) were followed by periods with low migration rates. Based on local channel morphology and LCM rates, 14 units were identified. The highest LCM rate was measured in the freely migrating units (R5: 5.8 m/y; R3: 4.4 m/y and R6 4.0 m/y).
Keywords: meandering, lateral channel migration, human impact, QGIS, topographic maps.